Corporate art collection practise in Malaysia: business managers and their rationales beyond the CSR idea - Selke, Raimond; Abdul Latiff, Ahmed Razman (Universiti Putra Malaysia Press, 2017)
The Malaysian concept of collecting Corporate Art remains underdeveloped, with only a few businesses supporting such engagement. Considerable research has been conducted to understand the management rationale for either engagement in collecting or avoiding art, although no such study is available relating to Malaysia. This research investigated the relationship between managers’ demographic backgrounds and the practise of collecting Corporate Art in Malaysia. Corporate Social Responsibility (CSR) and community engagement are the drivers behind organisational art acquisition. Art can also enhance other stakeholders’ benefits. This study used the Stakeholder Theory as theoretical framework, and the analyses used mainly t-Test and ANOVA. Major findings were that demographics influence the rationale behind Corporate Art Collection practice, and a positive correlation was found between the CSR rationale and other rationales such as Decoration or Cultural Experience. A model for the highest potential for art engagement in Malaysia was then derived: Managers who are Muslim, specializing in HRM, working in the Finance sector and are over 37 years old. The findings can create an awareness of Corporate Art Collection practise beyond the mainstream business of viewing it as an investment or solely as a CSR tool. The paper brings valuable knowledge to Malaysian managers and communication professionals with respect to the impact of brand and image extension strategies through artistic and cultural products.